Laboratório de figurinos: uma experiência criativa em sala de aula - Vasconcelos, Tainá Macedo (2016)
The developed research covers issues concerning of costume design, from the creative process and the organization of this activity, to seeking an appropriate space for the preparation and production of drama costumes. The costume design to theater is a subject with few studies, and the number of publications is still small. The aim is to collaborate with the research on this subject, and also assist the process of preparing costumes for the theater. Thus, this paper proposes the implementation of a laboratory of costume design in educational spaces, favoring artistic and aesthetic experience to the students. This laboratory allows many people to access creative processes of costume design. In this way, the school gets one more chance to study theater, and especially the costumes as an important element to the scene.